Current approaches for the exploration of antimicrobial activities of nanoparticles. Issue 1 (31st December 2021) - Rosli, Nur Ameera; Teow, Yeit Haan; Mahmoudi, Ebrahim
ABSTRACT: Infectious diseases of bacterial and viral origins contribute to substantial mortality worldwide. Collaborative efforts have been underway between academia and the industry to develop technologies for a more effective treatment for such diseases. Due to their utility in various industrial applications, nanoparticles (NPs) offer promising potential as antimicrobial agents against bacterial and viral infections. NPs have been established to possess potent antimicrobial activities against various types of pathogens due to their unique characteristics and cell-damaging ability through several mechanisms. The recently accepted antimicrobial mechanisms possessed by NPs include metal ion release, oxidative stress induction, and non-oxidative mechanisms. Another merit of NPs lies in the low likelihood of the development of microbial tolerance towards NPs, given the multiple simultaneous mechanisms of action against the pathogens targeting numerous gene mutations in these pathogens. Moreover, NPs provide a fascinating opportunity to curb microbial growth before infections: this outstanding feature has led to their utilization as active antimicrobial agents in different industrial applications, e.g. the coating of medical devices, incorporation in food packaging, promoting wound healing and encapsulation with other potential materials for wastewater treatment. This review discusses the progress and achievements in the antimicrobial applications of NPs, factors contributing to their actions, mechanisms underlying their efficiency, and risks of their applications, including the antimicrobial action of metal nanoclusters (NCs). The review concludes with a discussion of the restrictions on present studies and future prospects of nanotechnology-based NPs development. Graphical abstract: uf0001